Low Carbon Emission Shrimp Farming Development Model - Muhammad Rifqi; Rokhmad M Rofiq; Andi Rahman; Rizna Ayu Wardhana; Fitrina Nazar (Pusbindiklatren Bappenas, 2022)
Shrimp is a vastly strategic aquaculture commodity in Indonesia, most of which is produced for the export market; hence, competitiveness is the main key in the industry. With the increasing productivity of a shrimp farming area, the regulation for establishing a shrimp culture area needs to be strictly managed, including reducing carbon emissions. The management of aquaculture areas needs to pay attention to the principle of sustainability and consider carbon dynamics. This paper contains a descriptive analysis of the literature related to the substance of the study. The carbon dynamics in aquaculture areas consist of potential sources of carbon emitted and potential sinks or carbon that can be absorbed and stored. By structuring the shrimp pond area, aquaculture engineering, the application of good aquaculture practices and use of alternative energy sources, during the shrimp farming process in ponds, the carbon emission can be minimized, and the carbon sink can be increased. Our recommendation suggests that analysis of land suitability, environmental carrying capacity and carbon dynamics in each shrimp pond area are exceptionally required to be conducted to assess land suitability as a low carbon emission shrimp farming area. Furthermore, to increase farmers' understanding and awareness of the sustainability of the practices, pilot areas for low-emission shrimp ponds need to be developed.